Limited reliability of radiographic assessment of spinal progression in ankylosing spondylitis - ALİBAZ ÖNER, FATMA (OXFORD UNIV PRESS, 2017)
Objectives. Conventional radiography is key to assessing AS-related spinal involvement and has become increasingly important given that spinal fusion may continue under biologic therapy. We aimed to compare the reliability of radiographic scoring of the spine by using different approaches to understand how different readers agree on overall scores and on individual findings. Method. Six investigators scored 68 plain radiographs of the cervical and lumbar spine of 34 patients with a 2-year interval, for erosions, sclerosis, squaring, syndesmophytes and ankyloses using the Spondyloarthritis Radiography (SPAR) module. The intraclass correlation coefficients were calculated compared with two gold standards. The reproducibility of each finding in 1632 vertebral corners and new syndesmophytes in each corner was calculated by kappa analysis and positive agreement rates. Results. The intraclass correlation coefficients mostly revealed good to excellent agreement with the gold standards (0.69-0.95). The kappa analysis showed worse agreement, being relatively higher for syndesmophytes (0.163-0.559) and ankylosis (0.48-0.95). Positive agreement rates showed that erosions were never detected at the same vertebral corner by two readers (positive agreement rate: 0%). The mean (range) positive agreement rates were 10.1% (0-27.7%) for sclerosis and 19.2% (0-59.7%) for squaring, and were higher for syndesmophytes [38.8% (21.4-62.5%)] and ankylosis [77.3% (64-95.3%)]. Conclusion. Our results show that there is a poor agreement on the presence of grade 1 lesions included in the Modified Stoke Ankylosing Spondylitis Spine Score-mostly for erosions and sclerosis-which may increase the measurement error. The currently used definitions of reliability have a risk of overestimating reproducibility.
Keywords: radiographic scoring; spine; ankylosing spondylitis; reproducibility; RADIOLOGY INDEX; HIGH AGREEMENT; BONE-FORMATION; LOW KAPPA; PARADOXES